ETIKA DI TENGAH BISNIS YANG MENGGLOBAL & PANDANGAN-PANDANGAN AGAMA - Muhlis, Muhlis; Anas, Anas (Universitas Muhammadiyah Makassar, 2021)
Realizing business developments that are growing rapidly and becoming increasingly globalized, of course, it requires business signs in the form of the application of business ethics that are not only concerned with personal interests or a few people but also pay attention to the consequences as well as the public interest and the business environment. For this reason, the purpose of this paper is to find out whether business people around us use ethics in running their business, then how business people realize how important the role of ethics in carrying out an increasingly global business is. The research model used uses research literature through descriptions based on library sources. Based on the analysis used by business people, there are still many who do not and do not understand how important it is to use ethics, that they do not realize how important ethics are in doing business, especially today, with an increasingly globalized business. Business ethics should be realized to be applied to people who carry out business activities based on the Qur'an and Al Hadith, there is no reason to reject ethics in an increasingly globalized business world, even adherence to business ethics, in fact, is conducive to efforts to increase profits. entrepreneur or owner of capital. Likewise guarding and preventing crime both for business people and for consumers.